Islam and humanitarian affairs: The middle class and new patterm of social activism - Hilman Latief (Islam and Humanitarian Affairs, 2013)
The major concern of this chapter is to discern the distinct nature of ‘Indonesian Islam’ by sketching the similarities and differences between Islamic social activism in Indonesia and that in other parts of the Muslim world.